2022
DOI: 10.1007/s11192-022-04388-5
|View full text |Cite
|
Sign up to set email alerts
|

Preprint citation practice in PLOS

Abstract: The role of preprints in the scientific production and their part in citations have been growing over the past 10 years. In this paper we study preprint citations in several different aspects: the progression of preprint citations over time, their relative frequencies in relation to the IMRaD structure of articles, their distributions over time, per preprint database and per PLOS journal. We have processed the PLOS corpus that covers 7 journals and a total of about 240,000 articles up to January 2021, and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The “never tried” responses were excluded from the analysis. The number of clusters was determined based on the dendrogram and assessment of the scree plot ( 43 ). The identified tastes were allocated to individual food items in the NDNS.…”
Section: Discussionmentioning
confidence: 99%
“…The “never tried” responses were excluded from the analysis. The number of clusters was determined based on the dendrogram and assessment of the scree plot ( 43 ). The identified tastes were allocated to individual food items in the NDNS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current study revealed a prevalence of neuroscience researchers citing preprints throughout their publications, with a particular emphasis in the introduction section. It is important to note that introductions typically contain more citations than other sections to establish context and prior research (Bertin & Atanassova, 2022). However, Bertin and Atanassova's (2022) research on examination of PLOS journal citations indicated a higher frequency of preprint citations within the methodology section.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that introductions typically contain more citations than other sections to establish context and prior research (Bertin & Atanassova, 2022). However, Bertin and Atanassova's (2022) research on examination of PLOS journal citations indicated a higher frequency of preprint citations within the methodology section. Note that the current research considers absolute number, but Bertin and Atanassova's (2022) research considered relative number (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations